Avaliação da virulência e da patogenicidade de cepas de Entamoeba dispar associadas com a Escherichia coli enteropatogênica (EPEC) sobre o abscesso hepático amebiano: estudo in vitro e in vivo - Cézar Augusto Vilela da Silva (2022)
Amebiasis is considered the second leading cause of death from parasitic diseases in the world. Entamoeba dispar is related to asymptomatic cases but has already been isolated from patients with non-dysenteric colitis and amoebic liver abscess (AHA). Bacteria can potentiate the virulence of E. dispar strains, and enteropathogenic Escherichia coli (EPEC) is an important cause of diarrhea. There are no studies evaluating the influence of this bacterium on the virulence and pathogenicity of E. dispar strains. The objective of this work was to evaluate the influence of EPEC on the virulence and pathogenicity of E. dispar strains. The ACFN, ADO and VEJ strains of E. dispar were used, divided into two groups: amoeba and amoeba+bacteria. In the associated groups, 1x106 CFUs of EPEC were added to the trophozoite culture. The erythrophagocytosis assay of the ACFN and ACFN-EPEC groups was performed. rt-qPCR was performed to analyze the gene expression of the virulence factors: Galactose and N-acetyl-d-galactosamine binding lectin (Gal/GalNAc), cysteine proteinase 2 (CP2), amoebapore A (APA) and amoebapore C (APC) of the ACFN, ADO and VEJ strains, associated or not with EPEC. For each group, eight hamsters were inoculated with the ACFN and ADO strains, associated or not with EPEC, each with 1x105 trophozoites, in the left lobe of the liver. The hamsters were euthanized and necropsied on the fourth day after infection and the inoculated hepatic lobe was collected for rt-qPCR analysis of the expression of the virulence factors lectin-binding Gal/GalNAc, CP2, APA and APC, biochemical determination of myeloperoxidase activity (MPO), N-acetyl-β-D-glucosaminidase (NAG) and eosinophil peroxidase (EPO) and digital morphometry of the lesions. The interaction of EPEC with the ACFN strain was not able to increase its erythrophagocytosis capacity, but it increased in vitro and in vivo the expression of the Gal/GalNAc-binding lectin and in vivo of CP2, the area of hepatic necrosis and the activity of MPO, NAG and EPO. The interaction of EPEC with the ADO strain decreased the expression of CP2 in vitro and was not able to increase the expression of the Gal/GalNAc-binding lectin and CP2 in vivo, as well as the area of necrosis and the activity of MPO and EPO. However, such interaction was able to decrease NAG activity. The interaction of EPEC with the VEJ strain was not able to increase the expression of the Gal/GalNAc binding lectin and CP2 in vitro. APA was not expressed in any of the evaluated strains and there was no difference in APC expression between any of the groups. Our study demonstrated that EPEC was able to influence in different ways the virulence and pathogenicity of different strains of E. dispar.